A Content Analysis of "Joyful" English Textbook for Primary Grade II - Vivin Sunarko; Nani Haro; Ira Tresnawati Sitorus; Pingky Ayu Sitorus; Erikson Saragih (Journal of English Education, 2019)
It is widely known that textbook holds an important role as one of learning sources in education. Textbooks used in schools must be compatible with 2013 curriculum, the newest curriculum applied in Indonesia. But it is found that some teachers complained how the content of textbooks doesn’t fit the objectives specified in 2013 curriculum. Therefore, research regarding analysis of textbook content feasibility is crucial to be conducted to decide whether a particular textbook feasible to be used for academic purposes. In this research, the researchers chose “Joyful” English textbook for Primary Grade II as the research object. The analysis was based on BSNP textbook content feasibility rubric which includes the compatibility of materials with KI and KD, the accuracy of materials and supporting materials. The aim of this research is to know how “Joyful” English textbook for Primary Grade II fulfill the textbook content feasibility specified in 2013 curriculum. Qualitative approach was applied in this research. The method used was content analysis method. In collecting the data, the technique used by the researchers was documentation. The data was analyzed using document checklist and percentage formula. The results showed that “Joyful” English textbook for Primary Grade II fulfills the textbook content feasibility by 79,17% so it was concluded that “Joyful” English textbook for Primary Grade II is feasible to be used at schools. However, because it isn’t 100% feasible, the researchers encouraged English teachers who want to use “Joyful” English textbook for Primary Grade II to cover the weaknesses by finding another learning source relevant to the learning objectives specified in 2013 curriculum.